2007
DOI: 10.1074/jbc.m705875200
|View full text |Cite
|
Sign up to set email alerts
|

The High Mobility Group Box Transcription Factor Nhp6Ap Enters the Nucleus by a Calmodulin-dependent, Ran-independent Pathway

Abstract: A gradient of Ran⅐GTP typically regulates traffic through the nuclear pore by modulating association of receptors with cargo.However, here we demonstrate that the yeast high mobility group box transcription factor Nhp6Ap enters the nucleus via a novel nuclear localization signal recognized by calcium calmodulin in a process that does not require Ran. Calmodulin is strictly required for the nondiffusional nuclear entry of Nhp6Ap. Calmodulin and DNA exhibit mutually exclusive binding to NHP6A, indicating that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…For example, the glucocorticoid receptor possesses two nuclear localization signals, one of which (NL1) appears to mediate the nuclear translocation of the unliganded receptor and requires binding to importin ␣, whereas the other (NL2) appears to mediate slower translocation of the receptor, a phenomenon that is agonist-specific and independent of binding to importin ␣ (62). Mammalian high mobility group box transcription factors also possess two nuclear localization signals, one that is a classical RanGTP-dependent signal and a second one that binds calmodulin (68). In our work, mutations in any of the nuclear localization signals in Nrf2 resulted in its failure to localize to the nucleus as well as in its failure to transactivate ARE-driven reporter gene constructs, indicating that all three nuclear localization sequences in Nrf2 are critical for the nuclear import and function of this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the glucocorticoid receptor possesses two nuclear localization signals, one of which (NL1) appears to mediate the nuclear translocation of the unliganded receptor and requires binding to importin ␣, whereas the other (NL2) appears to mediate slower translocation of the receptor, a phenomenon that is agonist-specific and independent of binding to importin ␣ (62). Mammalian high mobility group box transcription factors also possess two nuclear localization signals, one that is a classical RanGTP-dependent signal and a second one that binds calmodulin (68). In our work, mutations in any of the nuclear localization signals in Nrf2 resulted in its failure to localize to the nucleus as well as in its failure to transactivate ARE-driven reporter gene constructs, indicating that all three nuclear localization sequences in Nrf2 are critical for the nuclear import and function of this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins are even imported without Ran (31,32), and there are even examples of proteins, such as ␤-catenin, whose transport seems to require neither importins nor Ran as these proteins can bind directly to the nuclear pore (33). We found that Npa3 can also bind at least one nuclear pore protein, Nup133, and although Nup133 is not one of the several phenylalanine-glycine repeat nucleoporins that have so far been implicated in the binding and translocation of import complexes, it is possible that Npa3 can directly bind nuclear pore proteins and therefore does not depend on the classical nuclear import pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ca 2ϩ -CaM has been shown to stimulate the nuclear localization of many proteins (58). In a recent report concerning the Ca 2ϩ -CaM-dependent nuclear entrance of the transcription factor Nhp6Ap it has been found that an unknown third protein is recruited through Ca 2ϩ -CaM binding and that a ternary complex is formed to facilitate transport across the nuclear pore (59). Consequently, the identification of proteins that can strongly and selectively interact with the N-lobe of Ca 2ϩ -CaM will be key to understanding the links between the MAPK cascade and the Ca 2ϩ signaling pathways in plants.…”
Section: Camentioning
confidence: 99%